THE TECHNOLOGY OF EXPERIENCE: NARRATIVE VS MEDIA ANALYSIS OF BASTILLE DAY, NICE, FRANCE 2016 - Archee, Ray (PEOPLE: International Journal of Social Sciences, 2019)
Humans possess the ability to experience life events and their accompanying emotions, to store these experiences in memory, and to create new behaviour in the future. It is often said that we learn best from our mistakes. However, life-threatening events are different. Extreme experiences can produce recurring memories that can lead to a range of stress disorders. In the present day many of our experiences and memories are being expanded and transformed by technology, especially the Internet. The author was a survivor of the lone terrorist attack on Bastille Day, 2016 in Nice, France. Two years later, this paper poses autobiographical narration to recount the experiences surrounding this incident and its aftermath. The author concurrently analyses the central narrative to juxtapose official accounts, media reports and reflection. The paper thus accomplishes two goals: it presents a first-hand experience of a major terrorist attack, and it compares a conscripted secondary version mediated by technology.